Commercial Sex Workers Policy in Indonesia - Kojongian, Rahayu; Halim, Hamzah; Sampurno, Slamet; Sakharina, Iin Karita (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze the reformulation of criminal liability for commercial sex workers. The method used in this study is an empirical normative research method. The results of the study indicate that the regulations to ensnare prostitutes in Indonesia have not been able to provide a deterrent effect. The Criminal Code can only be used to ensnare a pimp / pimp / commercial sex worker provider. whereas Articles that can be used to ensnare commercial sex workers are regulated in their respective regional regulations. Based on the principle of lex superior derogat legi inferior, of course, the regulation on prohibition of prostitution cannot be enforced because it is against the Criminal Procedure Code as a higher law. The clash between prostitution activities with moral values, religion, and culture certainly becomes a philosophical and sociological problem in building an ethical, cultured, and civilized society. Law Enforcement in the process of providing sanctions to prostitution perpetrators of law enforcement officers is in accordance with applicable regulations. it’s just that we need a reformulation of criminal responsibility aimed at commercial sex workers too. where in the case what happens is that commercial sex workers knowingly and without coercion practice prostitution. The absence of rules that explicitly prohibit the practice of prostitution, is an obstacle so that the practice of prostitution is increasingly increasing with various types of types of prostitution along with the development of the era. Efforts made in providing sanctions for the responsibility of commercial sex workers from existing cases only by making them as witnesses and victims, as well as data collection and then the commercial sex workers were given rehabilitation only